Participative Leadership and the Organizational Commitment of Civil Servants in China: The Mediating Effects of Trust in Supervisor. (7th August 2013) - Miao, Qing; Newman, Alexander; Schwarz, Gary; Xu, Lin
Abstract : The present study examines whether participative leadership engenders organizational commitment amongst Chinese civil servants and analyses the mechanisms by which it transmits its effects. Confirmatory factor analysis and structural equation modelling revealed that there was a significant relationship between supervisor‐level participative leadership and the affective and normative commitment of subordinates, but no relationship with continuance commitment. Affective trust was also identified as the mediator variable underlying the relationship between participative leadership and organizational commitment. We show that participative leadership of supervisors elicits higher levels of trust and leads subordinates to reciprocate through exhibiting higher levels of organizational commitment. Our study also reveals that Chinese civil servants who accept an unequal distribution of power between supervisors and subordinates typically exhibit lower levels of affective and normative commitment to the organization than those who do not. Our results provide greater support for the deepening of administrative reforms and the dissemination of participative leadership practices in China's new civil service system.